EXAMINING THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING PERSONALIZATION STRATEGIES AND CUSTOMER EXPERIENCE IN E-COMMERCE - G Mukund; Tripathi, Harshit (International Journal of Research -GRANTHAALAYAH, 2024)
The swift development of e-commerce has made it highly significant that businesses are able to provide extremely customized shopping experiences to maintain the level of customer loyalty and elevate the level of satisfaction. The tool of Artificial Intelligence (AI) has become a decisive instrument in advancing personalization strategies based on the data analytics, machine learning, and predictive algorithms. This study explores the use of AI to understand how it can be used to improve personalization and make the customer experience better in online stores. The goal of the study is to examine the different AI technologies that have been implemented to achieve personalization, how they have affected customer engagement and customer satisfaction and the challenges and practices linked with the deployment of AI solutions such as ethical considerations and data privacy considerations. Drawing upon the present practices and the results, the study offers clues to the opportunities of integrating AI strategically to maximize the level of personalization, to provide excellent customer experience, and to remain competitive in the digital market. It is assumed that the findings will add to the academic knowledge as well as the practical implementation of AI-based personalization in e-commerce.